Contribution of the alternative model for DSM-5 personality disorders to relationship satisfaction - Savard, Claudia; Deschênes, Mélissa; Gagné-Pomerleau, Élodie; Payant, Maude; Mayrand, Kristel; Nolin, Marie-Chloé; Marcoux, Louis-Alexandre; Gamache, Dominick (Frontiers in Psychiatry, 2024)
Many studies showed that personality is a central factor associated with relationship discord, conflicts, and separation, as well as with dyadic adjustment and relationship stability. The Alternative Model for Personality Disorders (AMPD) of the DSM-5 offers a hybrid model for understanding personality based on personality dysfunction (Criterion A) and pathological personality domains and facets (Criterion B). So far, few studies have integrated this model into the understanding of relationship quality. Therefore, the aim of this study was to examine the contribution of Criteria A and B, as well as their interaction effects, to dyadic adjustment in individuals involved in an intimate relationship. Method. Participants were drawn from two clinical samples: patients with personality disorders (PD; N = 101) consulting in a day hospital treatment program, and clients consulting in private practice clinics (PPC; N = 350). They completed self-report questionnaires assessing AMPD Criteria A (only for PPC sample) and B, and dyadic adjustment. Results. Multiple linear regressions showed that, for the PD sample, Detachment and Negative Affectivity domains, and especially pathological facets of Intimacy Avoidance and Separation Insecurity, explained 23.1% of dyadic adjustment's variance. For PPC clients, Detachment, Negative Affectivity, and Antagonism domains, and especially pathological facets of Intimacy Avoidance, Anhedonia, and Grandiosity contribute significantly to dyadic adjustment, explaining 14.8% of its variance. No Criterion A and B interaction effects were found.Overall, these results support that the AMPD is an informative and useful model for identifying